The Effects of Top Management Team Integrative Complexity and Decentralized Decision Making on Corporate Social Performance - Wong, Elaine M.; Ormiston, Margaret E.; Tetlock, Philip E. (Academy of Management Journal, 2011)
We examine the influence of top management teams' (TMTs') integrative complexity and decentralization of decision making on corporate social performance. We argue that both factors increase TMT ability to gather information on, and attend to, stakeholder needs, thereby yielding higher corporate social performance. We further predict that decentralization moderates the relationship between integrative complexity and corporate social performance in such a way that the relationship is stronger under conditions of centralization. Using a Q-sort methodology, which translates complex qualitative observations into quantitative metrics, we examined integrative complexity and decentralization in 61 Fortune 500 firms and found support for our predictions.